Effect of early administration of dexamethasone in patients with COVID-19 pneumonia without acute hypoxemic respiratory failure and risk of development of acute respiratory distress syndrome: EARLY-DEX COVID-19 trial - Franco-Moreno, Anabel; Acedo-Gutiérrez, María Soledad; Casado-Suela, Miguel Ángel; Labrador-San Martín, Nicolás; de Carranza-López, María; Ibáñez-Estéllez, Fátima; Hernández-Blanco, Clara; Jiménez-Torres, José; Vallejo-Maroto, Ignacio; Romero-Pareja, Rodolfo; Peña-Lillo, Gabriela; Escobar-Rodríguez, Ismael; et al. (Frontiers in Medicine, 2024)
Nº of Additional File: 1 (4.7%), with four in the treatment group and two in the control group. There were no deaths during hospitalization or during follow-up. An intermediate analysis for futility showed some differences between the control and treatment groups (Z=0.0284).However, these findings were within the margins close to the region where the null hypothesis would not be rejected.: In patients with COVID-19 pneumonia without oxygen needs but at risk of progressing to severe disease, early dexamethasone administration did not lead to a decrease in ARDS development. tre Trial registration: ClinicalTrials.gov NCT04836780. Registered on 8 April 2021 as EARLY-DEX COVID-19.